(untitled) (Economics and region, 2019)
Mechanism of ensuring dynamic and modern development of national economy and its enterprises was determined in the article. Such mechanism is the “turnkey” implementation of strategic programs and projects for creation in Ukraine of high-tech research and production systems. A model and algorithm for implementation of this mechanism based on world standards for strategic, multi-project and project management of scientific, technical and high-tech progress in advanced sectors of Ukraine’s economy, its regions, companies and so on were proposed.